2009
DOI: 10.1371/journal.pone.0006230
|View full text |Cite
|
Sign up to set email alerts
|

Eyes Wide Shut: Amygdala Mediates Eyes-Closed Effect on Emotional Experience with Music

Abstract: The perceived emotional value of stimuli and, as a consequence the subjective emotional experience with them, can be affected by context-dependent styles of processing. Therefore, the investigation of the neural correlates of emotional experience requires accounting for such a variable, a matter of an experimental challenge. Closing the eyes affects the style of attending to auditory stimuli by modifying the perceptual relationship with the environment without changing the stimulus itself. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 70 publications
3
42
0
1
Order By: Relevance
“…Additionally, in a hypervigilant state and with their eyes closed, patients may have become more attentive to sounds within the unfamiliar environment. In line with this suggestion, a recent combined fMRI/EEG study found that auditory information was more negatively appraised and was associated with increased activity in the amygdala and associated areas, during REC compared to REO (Lerner et al, 2009).…”
Section: Globally-reduced Spectral Power In Pdmentioning
confidence: 71%
“…Additionally, in a hypervigilant state and with their eyes closed, patients may have become more attentive to sounds within the unfamiliar environment. In line with this suggestion, a recent combined fMRI/EEG study found that auditory information was more negatively appraised and was associated with increased activity in the amygdala and associated areas, during REC compared to REO (Lerner et al, 2009).…”
Section: Globally-reduced Spectral Power In Pdmentioning
confidence: 71%
“…Another putative confound constitutes the instruction of keeping eyes closed during stimulus presentation. A recent neuroimaging study showed that closing the eyes while listening to emotional music, resulted in enhanced ratings of emotionality and greater activation of the amygdala (as well as Locus Coeruleus and Ventral Prefrontal Cortex) [56]. Moreover, as compared to healthy controls and patients with obsessive compulsive disorders, DPD patients showed reduced neural activation for affective visual stimuli in regions involved in visual processing (middle and superior temporal gyri), which might reflect lower attention to aversive stimuli [19].…”
Section: Discussionmentioning
confidence: 99%
“…These responses often depend on the valence of the stimulus, increasing with negative (e.g., fearful, sad) music and decreasing with pleasant music (Blood and Zatorre, 2001; Baumgartner et al, 2006; Koelsch et al, 2006; Mitterschiffthaler et al, 2007; Lerner et al, 2009). Blood and Zatorre reported that during listening to pleasurable music, rCBF in the amygdala was inversely related to that in the area containing the nAc.…”
Section: Discussionmentioning
confidence: 99%